EFFECT OF INTEGRATED MODULES OF YOGIC PRACTICES AND DIET ON STRESSED TYPE II DIABETES - Amit Kumar Shaw, Dr. S. Murugesen (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
The purpose of the present study is to find out the effect of Integrated modules of yogic practices with and without diet on the risk factors among the Type II Diabetes. The study is conducted on 45 Type II Diabetes in totally three groups, namely, experimental group – I & II and Control Group, each group consisted of 15 Type II Diabetes. They underwent twelve weeks of practice in Pawanamuktasana series, Asana, Pranayama, Meditation and Relaxation with and without diet of both the experimental groups whereas the control group do not undergo any type of training. The stress of the Psychological variables are measured before and after using the standard questionnaires (Dr.Latha Sathish Questionaire). The Analysis of Covariance (ANCOVA) analyzes the data and it is concluded that the Pawanamuktasana series, Asana, Pranayama, Meditation and Relaxation with diet have a significant of (P < 0.05). Key words: Pawanamuktasana series, Asana, Pranayama, Meditation and Relaxation with diet and psychological variables.